KEPEMIMPINAN STRATEGIS DAN DISKRESI DOKTER HEWAN KARANTINA SULAWESI UTARA DALAM PENCEGAHAN ASF DI BANDARA SAM RATULANGI STUDI KASUS: PENGAWASAN KOMODITAS IMPOR TANPA DOKUMEN - Nathalia Wulandari; Lucky O.H. Dotulong; Genita G. Lumintang (Magister Manajemen Program Pasca Sarjana Universitas Sam Ratulangi Manado, 2026)
This research is motivated by the high frequency of international animal commodity traffic entering through Sam Ratulangi International Airport in Manado without quarantine documents from the country of origin. This situation poses a risk of the entry and spread of infectious animal diseases, particularly African Swine Fever (ASF), which threatens food security, animal health, and the stability of the national livestock economy. This study aims to analyze and describe the leadership strategy of the Head of the North Sulawesi Animal, Fish, and Plant Quarantine Agency (BKHIT) in strengthening human resource capacity and supporting the technical discretion of quarantine veterinarians in mitigating the risks of ASF prevention. The research method used was a qualitative approach with a descriptive case study design. Data were collected through in-depth interviews with key informants, field observations, and analysis of quarantine action documentation. The results of the study indicate that the effectiveness of law enforcement and preventive measures at the border is significantly supported by the five pillars of strategic leadership of the Head of the Center, namely: (1) strict enforcement of work discipline, (2) cross-agency communication and coordination strategies, (3) development of technical competencies of human resources, (4) legitimacy of risk-based decision-making, and (5) management of the emotional stability of the organization under work pressure. This study concludes that responsive and facilitative strategic leadership is the main foundation in optimizing quarantine discretion to maintain the biosecurity status of the region. Key words: Kepemimpinan Strategis, Diskresi, Dokter Hewan Karantina, African Swine Fever (ASF), Bandara Sam Ratulangi.